Dirt, Saliva and Leprosy: Anti-Inflammatory and Anti-Infectious Effects - Helieh S. Oz (Diseases, 2019)
Ancient Egyptians smeared a mixture of dark soil on their eyelids and believed it protected eyes from unknown forces (illness). Recent studies have proven that the dark soil across the Nile River is rich in natural compounds including lead sulfide, which in low levels, promotes the production of nitric oxide (240-fold) by keratinocytes, with strong immune stimulatory and antimicrobial properties. Current investigations reveal anti-inflammatory and anti-infectious activities—including cytokines and chemokines—in saliva, as well as its friendly microbiota, which lines the surface of the oral cavity, its protection against inflammatory and infectious organisms in the stoma and other organs, such as the cardiovascular and central nervous systems. In fact, saliva may soon become a safe and practical surrogate biomarker for genomic/proteomic evaluations and to replace painful blood drawing and its side effects. Another example is leprosy, or Hansen’s disease, a chronic inflammatory syndrome and neglected tropical disease, which affects the skin, and peripheral and trigeminal neurons causing a lack of sensation to heat and cold and loss of extremities. Leprosy has horrified humans for over 2000 years, as lepers were considered unclean sinners and were subsequently drawn out of towns. This communication scrutinizes the past and the present state of saliva and leprosy to encounter possible mystery and/or wisdom in ancient healing as the mixture of “sputum and dirt„ as reported in the biblical time.